2019
DOI: 10.1016/j.heliyon.2019.e01279
|View full text |Cite
|
Sign up to set email alerts
|

A new Mycobacterium leprae dihydropteroate synthase variant (V39I) from Papua, Indonesia

Abstract: Indonesia had the third highest number of new leprosy cases worldwide in 2017. This disease is still prevalent in Papua province, where the number of new cases in 2014 (3.0 cases per 10,000 people) is considered highly endemic and is well above the World Health Organization's (WHO) cutoff of <1 new case per 10,000 people. Since 1995, the WHO has supplied Papua province with a multi-drug therapy (MDT) in which multibacillary (MB) patients are treated with rifampicin, clofazimine, and dapsone and paucibacillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…To tackle, this the research is ongoing to inhibit the enzyme ribonucleotide reductase (RNR) because of its involvement in the biosynthesis of nucleotides [49,[75][76][77][78]. Many reports also suggested that the enzyme dihydropteroate synthase (DHPS) is also one of the important enzymatic targets [79,80]. Hence, we thought to include the details of the agent developed for inhibiting the RNR and DHPS action.…”
Section: Review Articlementioning
confidence: 99%
“…To tackle, this the research is ongoing to inhibit the enzyme ribonucleotide reductase (RNR) because of its involvement in the biosynthesis of nucleotides [49,[75][76][77][78]. Many reports also suggested that the enzyme dihydropteroate synthase (DHPS) is also one of the important enzymatic targets [79,80]. Hence, we thought to include the details of the agent developed for inhibiting the RNR and DHPS action.…”
Section: Review Articlementioning
confidence: 99%
“…Моментом начала химиотерапии лепры, несмотря на низкую эффективность лечения и многочисленные нежелательные эффекты для пациента, можно считать применение сульфонов [20]. Монотерапию лепры бактериостатическим препаратом дапсон (4, 4'-диаминодифенилсульфон) проводили с момента его открытия в 1935 г. Известно, что мишенью дапсона является дигидроптероатсинтаза, ключевой фермент в биосинтезе фолиевой кислоты у бактерий, включая M. leprae [21,22]. Особенностью метаболизма микобактерий является эндогенный синтез фолиевой кислоты, в то время как организм человека может усваивать фолиевую кислоту, поступающую извне.…”
Section: фармакотерапия лепрыunclassified
“…Самая распространенная мутация -это С/T транзиция (CCC→CTC) в 55 положении кодона, приводящее к замене лейцин→пролин (Leu→Pro), которая снижает эффективность терапии дапсоном [33] (таблица). Также обнаружена замена Val→Ile в 39 аминокислотной позиции дигидроптероатсинтазы, возникающая в результате трансверсии Т/А (GTC→GAC) [22].…”
Section: развитие устойчивости микобактерий лепры к антимикробной тер...unclassified
“…There are three DHPS catalytic active sites, pterin, pABA and anion-binding pocket, of which sulfa drugs mostly target pABA active site pocket (Achari et al, 1997;Babaoglu et al, 2004;Roland et al, 1979;Woods, 1940;Zhu and Stiller, 2001). The point mutations (at position 53 and 55) leading to drug resistance in M. Leprae are located near the pABA active site particularly at the flexible and conserved loops, which might influence the binding environment of the active site (Maladan et al, 2019;Matsuoka et al, 2007;Nakata et al, 2011). Moreover, the lack of availability of the crystal structure of M.leprae DHPS hampered the efforts to understand the structural basis of sulfa drug resistance and to discover novel inhibitors.…”
Section: Introductionmentioning
confidence: 99%